The Sensory Abnormality Mediated Partially the Efficacy of Repetitive Transcranial Magnetic Stimulation on Treating Comorbid Sleep Disorder in Autism Spectrum Disorder Children - Gao, Lei; Wang, Chen; Song, Xiao-rong; Tian, Li; Qu, Zhi-yi; Han, Yu; Zhang, Xin (Frontiers in Psychiatry, 2022)
Sleep disorder emerges as common comorbidity in children with autism spectrum disorder (ASD), and the interaction between the core symptoms of ASD and its sleep disorder remains unclear. The repetitive Transcranial Magnetic Stimulation (rTMS) was used on the bilateral dorsolateral prefrontal cortex (DLPFC) to investigate the efficacy of rTMS on the core symptoms of ASD and comorbid sleep problems, as well as the mediation role of the ASD symptoms between rTMS intervention and sleep improvement. There were 41 Chinese children with ASD who met the criteria of DSM-Ⅴwere recruited, and 39 of them (mean age: 9.0 ± 4.4 years old, the male-female ratio was 3.9: 1 ) completed the study with the stimulating protocol of high frequency on the left DLPFC and low frequency on the right DLPFC. They were all assessed three times (before, four weeks after, and eight weeks after the stimulation) by the Children's Sleep Habits Questionnaire (CSHQ), Strengths and Difficulties Questionnaire (SDQ), Childhood Autism Rating Scale (CARS), Repetitive Behavior Questionnaire-2 (RBQ-2) & Short Sensory Profile (SSP). The repeated measure ANOVA showed the main effect of "intervention time" of CSHQ (F=25.103, P<0.001), SSP (F=6.345, P=0.003), and SDQ (F=9.975, P<0.001) was statistically significant. By the Bayesian mediation analysis, we only found that the total score of SSP mediated the treating efficacy of rTMS on CSHQ (αβ =5.11±1.51, 95% CI: 2.50, 8.41), the percentage of mediation effect in total effect was 37.94%. Our results indicated the treating efficacy of rTMS modulation on bilateral DLPFC for both autistic symptoms and sleep disturbances, the sensory abnormality of ASD mediated the improvement of rTMS on sleep problems of ASD.